2021
DOI: 10.3390/e23010116
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Class Automatic Sleep Staging Method Based on Photoplethysmography Signals

Abstract: Automatic sleep staging with only one channel is a challenging problem in sleep-related research. In this paper, a simple and efficient method named PPG-based multi-class automatic sleep staging (PMSS) is proposed using only a photoplethysmography (PPG) signal. Single-channel PPG data were obtained from four categories of subjects in the CAP sleep database. After the preprocessing of PPG data, feature extraction was performed from the time domain, frequency domain, and nonlinear domain, and a total of 21 featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…As recently summarized in a comprehensive systematic review ( Imtiaz, 2021 ), PPG-based solutions are on average easier to use and better suited for wearable/nearable monitoring but often unable to reliably characterize the full spectrum of sleep stages. A recent manuscript by Zhao and Sun (2021) , proposed an approach similar to our work despite limited to a significantly smaller sample size. The reported results for accuracy and Cohen’s kappa of the 3-level and 4-level models are aligned with our findings.…”
Section: Discussionmentioning
confidence: 93%
“…As recently summarized in a comprehensive systematic review ( Imtiaz, 2021 ), PPG-based solutions are on average easier to use and better suited for wearable/nearable monitoring but often unable to reliably characterize the full spectrum of sleep stages. A recent manuscript by Zhao and Sun (2021) , proposed an approach similar to our work despite limited to a significantly smaller sample size. The reported results for accuracy and Cohen’s kappa of the 3-level and 4-level models are aligned with our findings.…”
Section: Discussionmentioning
confidence: 93%
“…Our validation study demonstrated that our SVM-based method was consistent with the AMI actigraph (accuracy = 94.4% ± 3.8%, specificity = 94.2% ± 5.2%, sensitivity = 94.8% ± 3.9%, and F1-score = 92.0 ± 4.5) ( 21 , 22 ). Note that while we used a classical machine learning approach for the sleep–wake classification, state-of-the-art methods, such as ensemble tree-based algorithms [e.g., extreme gradient boosting (XGBoost) ( 35 ), or light gradient boosting machine (LightGBM) ( 36 , 37 )], or deep neural networks [e.g., long short-term memory ( 38 40 )], may improve classification performance significantly.…”
Section: Methodsmentioning
confidence: 99%
“…By incorporating time information and replacing the classifier by conditional random fields, Cohen's kappa increased to 0.53 in 100 healthy subjects (Fonseca et al, 2018). In 2017, Tataraidze et al (2017) reported a kappa of 0.56 based on respiratory inductance plethysmography (RIP) signals using an extreme gradient boosting classifier in 658 healthy subjects and Beattie et al (2017) reported a kappa of 0.52 based on photoplethysmography (PPG) and actigraphy signals using a linear (Li et al, 2018;Radha et al, 2019;Wei et al, 2019;Sridhar et al, 2020;Huttunen et al, 2021;Zhao and Sun, 2021;Garcia-Molina and Jiang, 2022) and 0.47 ± 0.15 for 10 datasets with external testing (Fonseca et al, 2020;Sridhar et al, 2020;Sun et al, 2020b;Bakker et al, 2021;Garcia-Molina and Jiang, 2022).…”
Section: Agreement Between Sleep Parameters Derived From Cardiorespir...mentioning
confidence: 99%